2006
DOI: 10.1590/s0102-311x2006000700006
|View full text |Cite
|
Sign up to set email alerts
|

Cogitação e prática do aborto entre jovens em contexto de interdição legal: o avesso da gravidez na adolescência

Abstract: This article aims to unveil the notion of abortion as an element in young people's thoughts on teenage pregnancy. The study analyzes data from semi-structured interviews with 123 young men and women 18-24 years of age in Porto Alegre, Rio de Janeiro, and Salvador, Brazil, belonging to different social strata. Based on information concerning their affective, sexual, and reproductive circumstances, an abortion typology was established with a gradient ranging from considering the act to the attempt to materialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
31

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 6 publications
3
32
0
31
Order By: Relevance
“…An example is the study by Aquino et al (28) , who found a high prevalence of abortion among adolescents facing their first pregnancy. The lower rate of induced abortion reported by the females in the present study has also been found in other studies (29,30) in which abortion is most often reported by boys than by girls, perhaps because they are not sure if the abortion was really performed or do not necessarily feel involved or responsible. On the other hand, females are more discreet when reporting an abortion, which can be understood based on the fact that they experience a difficult process until making a decision.…”
Section: Discussionsupporting
confidence: 79%
“…An example is the study by Aquino et al (28) , who found a high prevalence of abortion among adolescents facing their first pregnancy. The lower rate of induced abortion reported by the females in the present study has also been found in other studies (29,30) in which abortion is most often reported by boys than by girls, perhaps because they are not sure if the abortion was really performed or do not necessarily feel involved or responsible. On the other hand, females are more discreet when reporting an abortion, which can be understood based on the fact that they experience a difficult process until making a decision.…”
Section: Discussionsupporting
confidence: 79%
“…In a population study on sexual, contraceptive and reproductive behavior of 2,991 women from 15 to 20 years in the National Demographic and Health Research of Children and Women, in 2006 , the poorest and least educated adolescents had more unprotected behavior, i.e., lowest percentage of contraceptive use at the first intercourse and at current use when compared to youngsters in better social conditions 14 . In Brazil, teenage pregnancy is related to lower family income, school dropout in primary education for both gender and higher possibility to perform abortions 14,29,30 . Moreover, early integration at work may induce maturity and the adoption of adult roles prematurely, besides reinforcing unhealthy behaviors and even stimulating the formation of a new family 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Sobre o processo da decisão em si, os escassos estudos sobre esta dimensão no país têm sido conduzidos, sobretudo, nas disciplinas das ciên-cias humanas, mediante pesquisas qualitativas 64,65 , considerando-se a dificuldade de abordar uma questão eminentemente subjetiva em estudos quantitativos. A construção da decisão deve ser compreendida como um processo, comportando idas e vindas, numa acumulação de fatores que podem culminar no aborto 55 .…”
Section: A Decisão Pelo Aborto Na Perspectiva Das Mulheresunclassified
“…A construção da decisão deve ser compreendida como um processo, comportando idas e vindas, numa acumulação de fatores que podem culminar no aborto 55 . Nesse sentido, Peres & Heilborn 65 , contrapondo-se a uma visão reducionista da decisão frente ao aborto, identificam um continuum entre não ter pensado na possibilidade do aborto, sua cogitação, tentativa e efetivação.…”
Section: A Decisão Pelo Aborto Na Perspectiva Das Mulheresunclassified